RUSSIAN MUSLIMS: HISTORY AND MODERN AGE (CASE OF ESTABLISHING AND DEVELOPING OF ISLAMIC COMMUNITY IN SAINT PETERSBURG) - M. A. Sapronova (Vestnik MGIMO-Universiteta)
Book review: Renat Bekkin, Almira Tagirdzhanova. Muslim Petersburg. Historical guide-book. The life of Muslims in St. Petersburg and its suburbs. - Moscow, St. Petersburg: Institute for African Studies, 2016. - 640p.